AP-1 regulates the expression of IL17-4 and IL17-5 in the pacific oyster Crassostrea gigas. Issue 97 (February 2020) - Wang, Liyan; Sun, Jiejie; Wu, Zhaojun; Lian, Xingye; Han, Shuo; Huang, Shu; Yang, Chuanyan; Wang, Lingling; Song, Linsheng
Abstract: The activator protein-1 (AP-1) plays an important role in inducing the immune effector production in response to cellular stress and bacterial infection. In the present study, an AP-1 was identified from Pacific oyster Crassostrea gigas (designed as Cg AP-1) and its function was investigated in response against lipopolysaccharide (LPS) stimulation. Cg AP-1 was consisted of 290 amino acids including a Jun domain and a basic region leucine zipper (bZIP) domain. Cg AP-1 shared 98.6% similarities with Ch AP-1 from oyster C. hongkongensis, and assigned into the branch of invertebrates in the phylogenetic tree. The mRNA transcripts of CgAP-1 gene were detected in all tested tissues with highest expression level in hemocytes, especially in granulocytes. The mRNA expression level of CgAP-1 gene in hemocytes was significantly up-regulated (8.53-fold of that in PBS group, p  < 0.01) at 6 h after LPS stimulation. Cg AP-1 protein could be translocated into the nucleus of oyster hemocytes after LPS stimulation. The mRNA transcripts of interleukin17s ( CgIL17-4 and CgIL17-5 ) in the hemocytes of CgAP-1 -RNAi oysters decreased significantly at 24 h after LPS stimulation, which were 0.37-fold ( p  < 0.05) and 0.17-fold ( p  < 0.01) compared with that in EGFP -RNAi oysters, respectively. The results suggested that Cg AP-1 played an important role in the immune response of oyster by regulating the expression of Cg IL17s. Highlights: Cg AP-1 identified in oyster was relatively higher expressed in hemocytes. The mRNA expression of Cg AP-1 in hemocytes was up-regulated after LPS stimulation. Cg AP-1 could translocate into hemocyte nucleus post LPS stimulation. Cg AP-1 could induce the expression of Cg IL17-4 and Cg IL17-5 after LPS stimulation.